Antitumor efficacy of the herbal recipe benja amarit against highly invasive cholangiocarcinoma by inducing apoptosis both in vitro and in vivo - Rittibet Yapasert (2020)
© 2020 by the authors. Thailand is the country with highest incidence and prevalence of cholangiocarcinoma (CCA) in the world. Due to the frequently late diagnosis that is associated with this disease, most CCA patients are prescribed chemotherapy as a form of treatment. However, CCA is able to resist the presently available chemotherapy, so to the prognosis of this disease is still very poor. In this study, we investigated the anticancer potential of a Thai herbal recipe, Benja Amarit (BJA) against CCA and the relevant mechanisms of action that are involved. We found that BJA inhibited CCA cell viability in a dose-dependent manner, especially in highly invasive KKU-213 cells. The extract induced mitochondrial-and caspase-dependent apoptosis in CCA cells by regulating the nuclear factor-κB (NF-κB) signaling pathway. BJA also triggered autophagy in CCA cells. Nonetheless, the inhibition of autophagy enhanced BJA-induced CCA cell death via apoptosis. An in vivo xenograft model revealed the growth-inhibiting and death-inducing effects of BJA against CCA by targeting apoptosis. However, general toxicity to blood cells, kidneys and the liver, as well as changes in body weight, did not appear. Our findings suggest that the herbal recipe BJA might be used as a potentially new and effective treatment for cholangiocarcinoma patients.